Psycho-spiritual elements evaluated by FACIT-Sp in stage IV cancer patients - Pedraz-Petrozzi, Bruno (2020)
Objective: To describe different psycho-spiritual elements in a sample of stage IV cancer patients from a public hospital in Lima, Peru, through the application of the Functional Assessment of Chronic Illness Therapy - Spiritual Well-Being (FACIT-Sp) scale. Methods: Application of FACIT-Sp to a sample of patients (n = 100) diagnosed with stage IV cancer at the Oncology Service of the Hospital Nacional Arzobispo Loayza. The 33-question instrument, designed to evaluate psycho-spiritual elements, analyzes five areas: social well-being (SWB), emotional well-being (EWB), functional well-being (FWB), meaning and peace (MP) and faith (F). Results: The most prominent aspect was F (average score=13.53 ± 3.05, corresponding to 84.56% of the maximum possible score), and the lowest was FWB (average score=15.79 ± 6.89, corresponding to 56.39% of the maximum possible score). Conclusions: According to FACIT-Sp, the most developed psycho-spiritual aspect among the participating patients was the one related to Faith, whereas the least developed, the one linked to the area of Functional Well-Being.